Analisis Perbandingan Pada Penjadwalan Job Untuk Ketepatan Waktu Proses - Pipit Sari Puspita (Jurnal Teknik Industri, 2007)
Almost most of company operates based on request (order). The aim of company in industry world is get to complete the customer needs that are the high quality of goods, cheap goods price or finish and delivery product on time. To realize the mention the company must compose production planning hooked on scheduling of production. The scheduling in problems right now, there are excessively long delivery times and the large of total idle time. The Problems cause the height of production cost in company. To overcome the mention will conduct an approach of method that able to give job schedule more precise. The methods are Algorithm Heuristic Dispatching Rule Last Come First Serve, Algorithm Heuristic Dispatching Rule Shortest Processing Time, Algorithm Heuristic Dispatching Rule Longest Processing Time, Algorithm Heuristic Dispatching Rule Earliest Due Date, Algorithm Heuristic Dispatching Rule Slack Time, which one of the method will choose with criteria like minimize makespan, mean tardiness and total of idle time. So is obtained result of new method which give minimize of the criteria is Algorithm Heuristic Dispatching Rule Last Come First Serve for September 2007. With this method company can economize process time (makespan) 2 hours, mean tardiness 3,13 hours and total of idle time 26 hours. For October 2007 obtained new method which give minimize of the criteria is Algorithm Heuristic Dispatching Rule Longest Processing Time. With this method company can economize process time (makespan) 1,5 hours and total of idle time 19,5 hours.